Evaluating 12 Years of Implementing a Multidisciplinary Specialist Child and Adolescent Obesity Treatment Service: Patient-Level Outcomes - Wyse, Cathy; Case, Lucinda; Walsh, Órla; Shortall, Catherine; Jordan, Norah; McCrea, Lois; O'Malley, Grace (Frontiers in Nutrition, 2022)
1. Introduction: Childhood obesity is a chronic disease that requires multidisciplinary and specialist intervention to address its complex pathophysiology, though access to treatment is limited globally. Evaluating the impact of evidence-based interventions implemented in real-world clinical settings is essential, in order to increase the translation of research into practice and enhance child health outcomes. In Ireland, the National Model of Care for Obesity highlighted the need to develop and improve healthcare services for children and adolescents with obesity. Aims: This study aims to evaluate the impact of a family-based, Tier 3 multi-disciplinary child and adolescent obesity outpatient service (www.w82go.ie) on standardised body mass index (BMI-SDS). Methods: Following referral by paediatricians, patients were assessed by a paediatric multidisciplinary team (physiotherapist, dietician, and psychologist) and personalized obesity treatment plans were developed. Anthropometric and demographic information were recorded at baseline and final visit. Descriptive statistics were used to explore distribution, central tendency and variation in the demographic data, change in BMI-SDS over time was assessed using a t-test, and multiple linear regression analysis was used to investigate the association of demographic factors on the change in BMI-SDS. Results: The overall mean BMI-SDS reduction across the whole cohort (n=692) was -0.17 (95% CI = -0.20, -0.13; p < 0.001). Younger age at admission and longer duration of treatment were associated with greater BMI-SDS reduction but there was no significant association between change in BMI-SDS and any of the other parameters (deprivation score, treatment type, sex, obesity category at admission or presence of co-morbid condition). Conclusion: Engagement in a specialist paediatric obesity service was associated with reductions in BMI-SDS in children and adolescents with obesity.